The Effectivity of 3D Interactive Multimedia to Increase the Students’ Visuospatial Abilities in Molecular - Tamami, Abdul Aziz; Dwiningsih, Kusumawati (Universitas Pendidikan Ganesha, 2020)
This research and development aims to develop interactive 3D multimedia that appropriate to increase students’ visuospatial abilities at molecular shapes geometry studies. This research and development use the modified research and development 4D Thiagarajan design model that limiting until the development testing step. The descriptive qualitative analysis is used to assess the data result. The multimedia effectiveness is stated based on the increasing right-answered percentage and N-Gain score interpretation. The result shows that it has an increasing right-answered percentage > 50% in each test indicator and signification rate at range 0,5174 – 1,0000 in the medium until high level. The achievement of two kind effectiveness’ criteria can be stated that interactive 3D multimedia is appropriate as the effective learning media to increase student’s visuospatial abilities. Visual model in 2D and 3D utilization can aid the students’ representation skill, so that it can be applied to the other relevant matter.